Molecular Epidemiology of Infectious Bursal Disease Virus in Mizoram during 2021–2022 - Naveen, R. M.; Roychoudhury, P.; Subudhi, P. K.; Dutta, T. K.; Udaya, S. S. T. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during the tenure period January, 2021–March, 2022 from different regions of Mizoram where outbreaks suspected to be IBDV were screened by agar gel precipitation test (AGPT) for molecular characterization of circulating Infectious Bursal Disease Virus (IBDV) carried out by targeting partial VP2 gene. Out of 32 samples, 12 tissue samples were found positive and further confirmed by Reverse transcription-Polymerase Chain Reaction (RT-PCR). A total of 4 field tissue samples were sequenced and phylogenetic analysis was carried out and found that one of the sequences clustered in Very Virulent IBDV (VVIBDV) group with sequence similarity of 95.3–98.6% and matching only 90.8% sequence similarity with Georgia vaccine strain and 95.6% with earlier reported VVIBDV strain (2015) of Mizoram. Other 3 sequences clustered in the Classical IBDV (CIBDV) group with sequence similarity of 98.9–99.8%. Deduced amino acid sequence of present study VVIBDV strain showed a unique very virulent amino acid marker at position A-222, I-242, S-299 and serine heptapeptide indicating very virulent IBDV. However, one unique virulent amino acid marker showed substitution at position 294 where isoleucine substituted by valine indicating the circulating VVIBDV in the North-eastern state differs from other parts of India. This study demonstrated that both classical IBDV and Very Virulent IBDV belonging to serotype-1 were associated in the outbreak of Mizoram.